2021
DOI: 10.28982/josam.969519
|View full text |Cite
|
Sign up to set email alerts
|

Learning process and results in endoscopic saphenous vein harvesting technique

Abstract: All procedures in this study involving human participants were performed in accordance with the 1964 Helsinki Declaration and its later amendments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Likewise, a sub-analysis of 1,471 patients, who underwent CABG with the use of SVG, comparing EVH and open techniques from the ROOBY trial, showed no significant differences between groups in terms of death or major perioperative complications including reoperation, new mechanical support, cardiac arrest, coma, stroke, or renal failure requiring dialysis 17 . Interestingly enough however, in the subgroup of 894 patients with 1-year angiographic follow-up, SVG patency for EVH versus open technique was 74.5% and 85.2%, respectively 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a sub-analysis of 1,471 patients, who underwent CABG with the use of SVG, comparing EVH and open techniques from the ROOBY trial, showed no significant differences between groups in terms of death or major perioperative complications including reoperation, new mechanical support, cardiac arrest, coma, stroke, or renal failure requiring dialysis 17 . Interestingly enough however, in the subgroup of 894 patients with 1-year angiographic follow-up, SVG patency for EVH versus open technique was 74.5% and 85.2%, respectively 18 .…”
Section: Discussionmentioning
confidence: 99%